(untitled) - Abbadie, Luc (Comptes Rendus. Géoscience, 2025)
The French Minister for Research, Higher Education and Innovation, asked to Jean Jouzel to chair a working group to examine the issue of raising awareness and training all students in our higher education system in the major challenges of the ecological transition. A report was published in February 2022. The major recommendations were to propose to all students a core training on all aspects of ecological transition, knowledge and skils, in the very first years of their training pathway, to develop a programme approach in all higher education institutions with the support of students and to train university staffs.